INHIBITOR AND ENHANCER FACTOR CONSUMPTION RELATION WITH ANEMIA IN ADOLESCENT GIRLS - Amartha, Tecky Afifah Santy; Prastika, Dewi Andang; Astuti, Vina Aditya (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Adolescence is a golden period with optimal growth and development. At this time, teenagers have very important physical and psychological needs. Moreover, if there is malnutrition, one of the problems is anemia. Anemia is a global public health problem that affects adolescent girls, women of childbearing age, pregnant women, and children in developed and developing countries. This study aims to analyze the correlation between inhibitor and enhancer consumption and anemia in adolescent girls. This is a cross-sectional study conducted in Semarang City. Early adolescents ages 10 – 15 years old, and fulfill the inclusion and exclusion criteria were selected using a questionnaire. Consumption of inhibitors and enhancers of iron was measured using a semi-qualitative food frequency questionnaire. Anemia status was measured using a digital hemoglobin meter device. The Chi-square test and Fisher’s exact test were used to analyze the research data. The result of this study shows there is no significant correlation between the consumption of inhibitors and enhancers of iron toward anemia status among adolescent girls with p-values 0.158 and 0.744 α (CI:95%) respectively. Adolescents should be concerned about what they consume, and information about what food can enhance and obstruct iron should be socialized so they can wiser to reduce consuming inhibitors and increase consumption enhancers of iron.